Evaluation of brand equity in software companies: Case Study of Chargon - Hoseini, Ayat; Otarkhani, Ali; Shokouhyar, Sajad Shokouhyar (Journal of Entrepreneurship, Business and Economics, 2016)
IT industry especially the software industry is of the growing industries in the world which has grown considerably in recent years. In such circumstances, there will be some companies which want to differentiate themselves from competitors and create a unique and favorable position in the minds of their own enterprise customers; one way to create a sustainable competitive advantage in these mar-kets that already has been less discussed is the creation of brand equity. Thus, the aim of this study is to evaluate brand equity in software companies that Chargon Company was selected. The statistical population included managers of Chargon’s subsidiary companies and their users that given the un-limited society, Cochrane formula has been used in unlimited population to determine sample size. Due to the minimal amount of sample that is 386 questionnaires, 500 questionnaires were distributed in the population. Structural equation modeling approach and SmartPLS.2 were used to analyzing collected data. The results show that emotional variables affect value on brand equity is 0.64. Also functional variables affect value on brand equity is 0.89.market behavior variable plays a positive mediating role between emotional variables and brand equity. On the other hand market behavior plays a negative mediating role between emotional variables and brand equity. Considering t-values higher than 1.96, the significance of relationships obtained is confirmed in 95% confidence level. Research paper Reference to this paper should be made as follows: Hosseini, A, Otarkhani, A., Shokouhyar, S. (2016). “Evaluation of brand equity in software companies: Case Study of Chargon”, Journal of En-trepreneurship, Business and Economics, Vol. 4, No. 2, pp. 182–200.